“Barnperspektivet måste genomsyra allt vi gör” En studie om hälso-och sjukvårdkuratorers arbete med barn som anhöriga inom vuxenpsykiatrin i Region Skåne - Darwesh,Ula (2025)
This study aims to explore how healthcare counselors in adult psychiatry in Region Skåne work with children as next of kin and the limitations and opportunities they experience in implementing a child’s perspective. The study is based on six semi-structured interviews with healthcare counselors. The material was analyzed thematically with an inductive approach. The results indicate that healthcare counselors play a crucial role in making children visible and in supporting patients. However, their work is often hindered by limited time, lack of resources, and the risk of damaging the therapeutic alliance when mandatory reports of concern are required. A key finding is the decisive role of child representatives, who are expected to safeguard children’s rights while simultaneously managing the trust of the patient. Counselors also describe how a lack of time and resources means that structured manuals, such as Beardslee and Let’s Talk About Children, are often not fully implemented. Instead, they rely on previous experiences and professional judgment, which highlight a tension between standardized manuals and the practical realities of everyday work. To understand these dynamics, the analysis is primarily guided by the concept of scope of action, complemented by the framework of street-level bureaucracy, which encompasses notions of discretion and autonomy, as well as the concept of ethical dilemmas.
Keywords: health care counselor; children as next of kin; adult psychiatry; child perspective; child representative; limitations